Identification of a Molecular Latch that Regulates Staphylococcal Virulence. Issue 4 (18th April 2019) - Xie, Qian; Zhao, Aishan; Jeffrey, Philip D.; Kim, Minyoung Kevin; Bassler, Bonnie L.; Stone, Howard A.; Novick, Richard P.; Muir, Tom W.
Summary: Virulence induction in the Staphylococcus aureus is under the control of a quorum sensing (QS) circuit encoded by the accessory gene regulator ( agr ) locus. Allelic variation within agr produces four QS specificity groups, each producing a unique secreted autoinducer peptide (AIP) and receptor histidine kinase (RHK), AgrC. Cognate AIP-AgrC interactions activate virulence through a two-component signaling cascade, whereas non-cognate pairs are generally inhibitory. Here we pinpoint a key hydrogen-bonding interaction within AgrC that acts as a switch to convert helical motions propagating from the receptor sensor domain into changes in inter-domain association within the kinase module. AgrC mutants lacking this interaction are constitutively active in vitro and in vivo, the latter leading to a pronounced attenuation of S. aureus biofilm formation. Thus, our work sheds light on the regulation of this biomedically important RHK. Graphical Abstract: Highlights: Structure of the full HK module of the S. aureus histidine kinase AgrC The DHp-CA docking interaction precludes AgrC autophosphorylation R238-Q305 hydrogen bond is key to sequestering AgrC in its inactive state The conformation of the S helix and the stability of the DHp-CA interface are coupled Abstract : In this work, Xie et al. report the structure of a chimeric protein containing the complete HK module of AgrC, the histidine kinase involved in S. aureus agr quorum sensing. Structure-guided biochemical analysis reveals that activation of AgrC involves disruption of an intrasteric inhibitory docking interaction in the AgrC dimer.